Treatment of Acute Kidney Injury Using a Dual Enzyme Embedded Zeolitic Imidazolate Frameworks Cascade That Catalyzes In Vivo Reactive Oxygen Species Scavenging - Hou, Xinyue; Shi, Jianxiang; Zhang, Jie; Wang, Zhigang; Zhang, Sen; Li, Ruifeng; Jiang, Wei; Huang, Tingting; Guo, Jiancheng; Shang, Wenjun (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Significant advances have been made in recent years for the utilization of natural enzymes with antioxidant properties for the treatment of acute kidney injury (AKI). Owing to their limited cellular uptake, poor pharmacokinetic properties, and suboptimal stability, however, these enzymes have been of limited clinical utility. Herein, we employed a novel biomimetic mineralization approach to encapsulate catalase (CAT) and superoxide dismutase (SOD) in a zeolitic imidazolate framework-8 (ZIF-8), after which this obtained SOD@CAT@ZIF-8 complex was anchored with MPEG2000-COOH to yield an MPEG2000-SOD@CAT@ZIF-8 (PSCZ) composite. This composite was then utilized as a stable tool with antioxidant properties for the integrated cascade-based treatment of AKI, remarkably improved intracellular enzyme delivery. This dual-enzyme-embedded metal-organic framework was able to effectively scavenge reactive oxygen species synergistically. In conclusion, the ZIF-8-based “armor plating” represents an effective means of shielding enzymes with improved therapeutic utility to guide the precision medicine-based treatment of AKI.